Revisiting an Early Thule Inuit occupation of Skraeling Island, Canadian High Arctic - Howse, Lesley (Études/Inuit/Studies)

(untitled) (Association Inuksiutiit Katimajiit Inc., 2013)
This paper presents the faunal material excavated from an Early Thule Inuit semi-subterranean house, house 15, from the Skraeling Island site (SfFk-4). In an effort to understand how the occupants of the house interacted with animals, a fine-grained zooarchaeological analysis is employed. Patterning in taxonomic and bone modification frequencies, skeletal element distributions, and prey demography are discussed. Inuit oral histories, mythology, and ethnographic sources are used to help interpret the results of the analysis and reconstruct the group’s subsistence economy.